2020
DOI: 10.1002/star.201900212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Pressure Processing on Common Beans (Phaseolus Vulgaris L.): Cotyledon Structure, Starch Characteristics, and Phytates and Tannins Contents

Abstract: High pressure processing (HPP) is an emerging technology capable of promoting structural changes in food. This work studies the effect of HPP at room temperature (50 MPa/1 or 10 min and 600 MPa/1 min) on the cotyledon structure, starch characteristics, tannins, and phytates of common beans (Phaseolus vulgaris L.). The results show that all process conditions promote a partial disruption of the bean parenchymal cells, minor reduction in birefringence under polarized light microscopy and, for samples processed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…However, HPP is not fully explored despite its capability to reduce phytic acid (74%) content in pulses. A limited number of publications on phytic acid reduction with HPP have been published (Alsalman & Ramaswamy, 2020; Belmiro et al, 2020; Linsberger‐martin, Weiglhofer, Phan, Phuong, & Berghofer, 2013). In the HPP system, the sample is placed in a high‐pressure chamber.…”
Section: Degradation Of Phytic Acid In Pulses Through Different Posth...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, HPP is not fully explored despite its capability to reduce phytic acid (74%) content in pulses. A limited number of publications on phytic acid reduction with HPP have been published (Alsalman & Ramaswamy, 2020; Belmiro et al, 2020; Linsberger‐martin, Weiglhofer, Phan, Phuong, & Berghofer, 2013). In the HPP system, the sample is placed in a high‐pressure chamber.…”
Section: Degradation Of Phytic Acid In Pulses Through Different Posth...mentioning
confidence: 99%
“…Similarly, electromagnetic radiations also (microwave, gamma, X‐ray, and electron beam [EB]) can reduce the phytic acid levels by disrupting chemical bonds in their route (Bhat & Sridhar, 2009; Khosravi, Kiani, Dastar, & Showrang, 2017; Ibirinde et al, 2019; Patterson, Curran, & Der, 2017). On the other hand, the effects of ultrasound and high pressure on phytic acid reduction in pulses are still in the nascent stage of research and need further investigation (Belmiro, Tribst, & Cristianini, 2020; Mohammadi et al, 2021; Torrezan, Frazier, & Cristianini, 2010). For considerable phytic acid reduction, a combination of two or more treatments may be more successful than a single treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on physicochemical properties of common bean starch were limited to a few varieties. The previous studies on physicochemical properties of common bean starch only covered one, [7] or two, [10,11] or three, [8] or four varieties, [2] thus providing a rather limited profile for genetic diversity.…”
Section: Genetic Variation In Physicochemical Properties Of Starch Among Common Bean Varietiesmentioning
confidence: 99%
“…However, there are relatively few comprehensive and detailed reports on common bean starch quality. [6] Recently, some starch quality parameters were studied for one, [7] three, [8] four, [2] and five [9] common bean varieties mainly grown in North America and South America. These studies revealed low variation in starch properties among common bean varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to enhance the hydrolytic efficiency of beans several strategies and pre‐treatments have been investigated (Rui et al., 2012). Common beans require full hydration or soaking before any treatment process to reduce the tannin (anti‐nutritional compound) content and reduce the boiling time (Belmiro et al., 2020). The most common pre‐treatment applied to dry beans since humankind started considering them as food is applying high heat (boiling temperature) to cook the beans.…”
Section: Introductionmentioning
confidence: 99%